The Relationship between Gold and Oil Prices and the Stock Market Returns of Kazakh Energy Companies: Comparison of the pre-COVID-19 and post-COVID-19 Periods - Bekzhanova, Saule; Tayauova, Gulzhanat; Akhanov, Serik; Tuleshova, Gulnar B.; Bolganbayev, Artur; Moldogaziyeva, Gulnara M. (International Journal of Energy Economics and Policy, 2023)
This study analyzes the relationship between gold and oil prices and the stock market returns of Kazakh energy companies during and after the COVID-19 pandemic. We considered the period between 01.01.2020 and 31.12.2021 as the pandemic period and the period between 01.01.2022 and 31.03.2023 as the post-pandemic period. Then we performed a Granger causality analysis to identify the effect of gold and oil market returns on assets traded in the stock exchange. The data was retrieved from the website https://www.marketwatch.com/. Our findings are important in terms of proving the existence of an interaction between the Kazakhstan stock market and international markets. We have found that the gold prices had a causal effect on KZAP both in the pandemic period and in the post-pandemic period, while the oil prices had a causal effect on KZAP only during the pandemic period. We also found no causal effect of the international market prices on the KEGC and KZTO returns. However, this does not prove that there is no relationship between the international market returns and the returns of energy companies traded on the Kazakhstan stock exchange. The relationship between the international market returns and the returns of Kazakhstan stock market energy companies, if there is any, and whether it can be generalized to the long term can be analyzed by cointegration analysis and Vector Error correction model (VECM) methods.